Endogenous nitric oxide formation in cardiac myocytes does not control respiration during β‐adrenergic stimulation - Kohlhaas, M; Nickel, A; Bergem, S; Casadei, B; Laufs, U; Maack, C (Wiley, 2017)
Endothelial nitric oxide (NO) controls cardiac oxygen (O2) consumption in a paracrine way by slowing respiration at the mitochondrial electron transport chain. While NO synthases (NOSs) are also expressed in cardiac myocytes, it is unclear whether they control respiration in an intracrine way. Furthermore, the existence of a mitochondrial NOS is controversial. Here, by combining fluorescence imaging with electrical field stimulation, the patch‐clamp method and knock‐out technology, we determined the sources and consequences of intracellular NO formation during workload transitions in isolated murine and guinea pig cardiac myocytes and mitochondria. Using 4‐amino‐5‐methylamino‐2′,7′‐difluorofluorescein diacetate (DAF) as a fluorescent NO‐sensor that locates to the cytosol and mitochondria, we observed that NO increased by ∼12% within 3 min of β‐adrenergic stimulation in beating cardiac myocytes. This NO stems from neuronal NOS (nNOS), but not endothelial (eNOS). After patch clamp‐mediated dialysis of cytosolic DAF, the remaining NO signals (mostly mitochondrial) were blocked by nNOS deletion, but not by inhibiting the mitochondrial Ca2+ uniporter with Ru360. While in isolated mitochondria exogenous NO inhibited respiration and reduced the NAD(P)H redox state, pyridine nucleotide redox states were unaffected by pharmacological or genetic disruption of endogenous nNOS or eNOS during workload transitions in cardiac myoctyes. We conclude that under physiological conditions, nNOS is the most relevant source for NO in cardiac myocytes, but this nNOS is not located in mitochondria and does not control respiration. Therefore, cardiac O2 consumption is controlled by endothelial NO in a paracrine, but not intracrine, fashion.